PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR GURU SD SARASWATI 4 DENPASAR - Diputra, Alvan Anggara; Rahyuda, Agoes Ganesha Rahyuda (E-Jurnal Manajemen, 2016)
This study aimed to examine the effect of transformational leadership and job satisfaction on organizational commitment and organizational citizenship behavior. Research was conducted on elementary school teachers Saraswati 4 denpasar. The sampling method used in this study sample is saturated. Data were collected using the method of observation, interviews and questionnaires. Respondents of the study a total of 35 primary school teachers Saraswati 4 Denpasar. Data analysis techniques used in this research is the analysis of pathways. These results indicate that (1) transformational leadership has a direct influence on organizational commitment, (2) job satisfaction has a direct influence on organizational commitment, (3) the commitment the organization has a direct influence on OCB, (4) transformational leadership has a direct influence on OCB. (5) job satisfaction has a direct influence on OCB, (6) transformational leadership influence on OCB through organizational commitment of elementary school teachers Saraswati 4 Denpasar, and (7) job satisfaction influence on OCB through organizational commitment of elementary school teachers Saraswati 4 Denpasar.
Keywords: kepemimpinan transformasional; kepuasan kerja; komitmen organisasi; organizational citizenship behavior